2018
DOI: 10.1111/eve.12891
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risks of working with horses: A questionnaire survey of equine veterinary surgeons

Abstract: SummaryLimited scientific evidence from other countries and plenty of anecdotal evidence suggest that the risk of personal injury in equine veterinary practice is high. However, a comprehensive description of the types of risks to which equine veterinary surgeons expose themselves has not previously been available. The aim of this study was to quantify the number, types and causes of personal injury sustained by equine veterinary practitioners in the UK. An interview (and online) questionnaire-based survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 11 publications
3
32
0
Order By: Relevance
“…The additional comments made by respondents about injury to equine practitioners are in line with the findings of a recent study, with remarks about receiving orthopaedic surgery because of equine work, kicks (even during laparoscopic surgery), working through uncomfortable positions, having busy schedules; in one case, injury resulted in a surgeon having to attend an emergency center . Equine veterinary practice is one of the most hazardous civilian occupations, and equine practitioners can expect to sustain seven to eight injuries during their career, possibly even leading to hospitalization or loss of consciousness.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The additional comments made by respondents about injury to equine practitioners are in line with the findings of a recent study, with remarks about receiving orthopaedic surgery because of equine work, kicks (even during laparoscopic surgery), working through uncomfortable positions, having busy schedules; in one case, injury resulted in a surgeon having to attend an emergency center . Equine veterinary practice is one of the most hazardous civilian occupations, and equine practitioners can expect to sustain seven to eight injuries during their career, possibly even leading to hospitalization or loss of consciousness.…”
Section: Discussionsupporting
confidence: 70%
“…This is clearly a significant problem in human laparoscopic surgery. There are no published veterinary studies in which WRMD have been examined specifically with reference to laparoscopic surgery, although a survey of equine veterinarians revealed that theirs is one of the most hazardous civilian occupations, with a high rate of injury during surgeons’ careers . The objective of this study was to investigate the frequency and scope of WRMD in veterinary laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The peerreviewed results of this work are published free online. 1 It is worth noting that 85 per cent of all reported injuries did not affect the head and that 77 per cent of individual's worst reported injuries did not affect the head. The study did not record whether any of the head injuries had occurred in individuals who were wearing head protection, whether head protection had, or would have, altered the extent of the head injury or whether respondents had ever avoided injury as a result of wearing head protection.…”
Section: British Equine Veterinary Association (Beva) Responsementioning
confidence: 98%
“…Concerned about equine practitioner safety, BEVA and the Veterinary Defence Society commissioned, at significant expense, research into the occupational risks of working with horses. The peer‐reviewed results of this work are published free online 1 …”
mentioning
confidence: 99%
“…Domestic horses are generally very compliant animals [ 1 ], with an ethology that features exceptional behavioural flexibility and rapid habituation [ 2 ]. In the developed world, they are kept mainly as companion, leisure, or sporting animals rather than working animals and are handled by people with a diversity, and often paucity, of relevant skills [ 3 ]. Veterinary and husbandry interventions as simple as examinations or grooming can bring risks to human safety [ 4 ].…”
Section: Introductionmentioning
confidence: 99%